Post-pandemic challenges for learning communities - Kobylarek, Aleksander (Journal of Education Culture and Society, 2021)
This article presents the fundamental challenges facing education after the COVID-19 pandemic — technological, social, political and ecological. The author suggests that post-pandemic the most important problems will not be related to its effects, but to building civic and environmental awareness. Technological challenges, in the form of the necessity of expanding the repertoire of the technical means of education, and social challenges in the form of the need to rebuild relationships, were important in the pandemic phase, and their strongest impact was delineated at the very beginning. After a return to the new normality (however it may be defined), challenges of this type will not disappear completely, but their strength will become weaker when compared to the problems humanity has faced practically from the beginning of the 21st century.